Leep in the treatment of cin and its impact on the reduction of mortality of cervical cancer - Fernanda Villar Fonseca; Carlos Afonso Maestri; Sabrina Godoy Campos Oliveira; Natasha Sarmento Correia Araújo; Alexandre Gnoatto; Karla Teresa Muñoz Sanjinés Wilszek (DST, 2018)
Introduction: The adequate treatment of cervical intraepithelial neoplasia (CIN) is an important component of cervical cancer prevention programs and its inadequate management may increase the future risk of neoplasia. Objective: To evaluate the role of loop electrosurgical excision procedure (LEEP) conization in the treatment of CIN, in an important state capital in southern Brazil, and to determine the impact on reducing cervical cancer mortality in the next 20 years. Methods: A retrospective cohort study was conducted in patients who underwent CIN treatment from January 1999 to December 2007 at Erasto Gaertner Hospital, analyzing the treatment morbidity and recurrence rate of the disease, using the χ2 test for statistical analysis and p≤0.05. Results: A total of 1,550 women, between 14 and 93 years of age (35±11.42) were evaluated. Recurrence rate was 6.8%. The postoperative complications were 5.8% bleeding, 2% cervical stenosis and 2% infection. The cervical cancer mortality rate decreased from 12 to 3.8/100,000 women and there was an increase in the incidence of the lesion in situ as opposed to the reduction of other clinical stages. Conclusion: LEEP conization was proven to be a highly effective tool in CIN treatment, substantially contributing to the reduction of mortality from cervical cancer, justifying its use in a systematic way in prevention programs.